QUALITY OF LIFE AMONG A SAMPLE OF MENOPAUSAL WOMEN: PREDICTIVE ROLES OF LOCUS OF CONTROL AND LIFESTYLES - Nwonyi, Sampson K.; Okoye, Chidera F.; Oginyi, C.N Ronald; Ofoke, Sunday M; Nwankwo, Francisca; Oketa, Chibugo M. (EBSU Journal of Social Sciences and Humanities, 2024)
This study examined predictive roles of locus of control and life styles on quality of life among a sample of menopausal women. Self-determination theory of quality of life was adopted in the study. Participants were one hundred and fifty (150) menopausal women selected from Federal Medical Center Jalingo, Taraba State Nigeria. Participant’s ages ranged between 44 to 78 years with a mean age of 51.11 years (SD = 5.26). Cross sectional design was adopted. Three instruments were used for data collection. Menopause-Specific Quality of Life Questionnaire,Locus of Control Behaviour Scale, and Healthy Lifestyle Behaviors Scale (HLBS). Two hypotheses were tested. Hierarchical multiple regression was the main statistic used for data analysis. Result of a hierarchical Multiple Regression analysis showed that locus of control is a positively significant predictor of menopausal women quality of life. Life style is a significant predictor of menopausal women quality of life. One good nascent implication of the findings is that engaging in behaviours that are healthier and having higher locus of control increases quality of life of menopausal women. It is recommended that menopausal women be given orientation on the need for healthy living to overcome challenges associated with menopause; and that they should be made to understand the need for developing and maintaining high internal locus of control.